Mutations in the fourth β‐propeller domain of LRP4 are associated with isolated syndactyly with fusion of the third and fourth fingers. Issue 6 (22nd March 2018) - Sukenik Halevy, Rivka; Chien, Huan‐Chieh; Heinz, Bo; Bamshad, Michael J.; Nickerson, Deborah A.; ,; Kircher, Martin; Ahituv, Nadav
Abstract: Isolated hand syndactyly is a common limb malformation with limited known genetic etiology. We used exome sequencing to discover two novel variants, chr11 g.46896373C>G; p.D1403H and chr11 g.46893078G>T; p.Q1564K, in LRP4 in a child with isolated bilateral syndactyly of the third and fourth fingers. Each variant was inherited from a different parent and neither parent was affected. Variants in LRP4 have been previously associated with syndactyly in Cenani‐Lenz syndactyly syndrome and Sclerosteosis 2, but have not been reported in individuals with isolated syndactyly. LRP4 inhibits LRP6/LRP5‐mediated activation of canonical Wnt signaling and mediates sclerostin‐dependent inhibition of bone formation. p.D1403H and p.Q1564K are located within the fourth β‐propeller of the extracellular protein domain that has yet to be associated with human disease. Functional analyses of p.D1403H and p.Q1564K show that they significantly decrease LRP4's inhibition of Wnt signaling. These results suggest that variants in the fourth β‐propeller of the extracellular protein domain may cause a phenotype distinct from previously characterized LRP4 variants. Abstract : We report a child with isolated syndactyly of the third and fourth fingers with compound heterozygote non‐synonymous variants (p.D1403H and p.Q1564K) in LRP4 . Variants in LRP4 have been associated with syndactyly in Cenani‐Lenz syndactyly syndrome and Sclerosteosis 2, but not with isolated syndactyly. These variants are located within the fourth β‐propeller of the extracellular protein domain that has yet to be associated with disease. Functional analyses of these variants show that they significantly decrease LRP4's inhibition of Wnt signaling.